Tubular porous scaffold integrated with amnion as well as preparation method and application of tubular porous scaffold
The tubular porous scaffold prepared by integrating enzymatic dehydrogenase amniotic membrane with silk fibroin and gelatin solves the problems of insufficient bioinertness and bioactivity of existing materials in urinary tract scaffolds, and achieves the effects of urothelial regeneration and anti-fibrosis, which is suitable for ureteral defect repair.
Patent Information
- Application Number
- CN202511468001.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-12-19
AI Technical Summary
Existing biodegradable materials lack sufficient bioinertness and bioactive reaction sites when constructing urinary tract stents, resulting in poor urothelial regeneration and anti-fibrosis effects, and failing to meet the needs of complex remodeling of ureteral tissue.
A tubular porous scaffold (SGA) was prepared by integrating dAM (docyte amniotic membrane) with a solution of silk fibroin and gelatin using an integrase-freezing method, followed by freeze-drying, compression, and cross-linking. This process integrated dAM into the tubular porous scaffold composed of gelatin and silk fibroin, thus preserving the functional properties of dAM.
The prepared SGA stent has high suture strength, porous structure and dense surface, which can promote urothelialization, inhibit fibrosis and achieve scarless ureter repair, and has excellent blood compatibility and low toxicity.
Smart Images

Figure CN121154935A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of biological medicine, and particularly relates to a tubular porous scaffold integrated with amniotic membrane, a preparation method and application thereof. BACKGROUND
[0002] Long-segment ureteral defects are a severe challenge for urologists, often requiring complex surgical intervention. Traditional treatment methods, such as autologous tissue transplantation (e.g., small intestine and tongue mucosa) and orthotopic kidney transplantation, are accompanied by significant trauma and limited success rates. Biodegradable natural polymers such as gelatin, silk fibroin (SF) and hyaluronic acid have been used to construct ureteral scaffolds, showing good results. These materials have good biocompatibility, processability and controllable degradation rate, enhancing the regenerative capacity of the graft. Previous studies have shown that the naturally occurring RGD sequence promotes ureteral epithelial repair through the Integrin / MAPK signaling pathway. However, compared with autografts, the tissue regeneration effect of these scaffolds is still insufficient. This limitation is attributed to their biological inertness and insufficient reaction sites for the transplantation of bioactive substances, resulting in poor promotion of ureteral epithelial regeneration and anti-fibrotic effect.
[0003] In recent years, decellularized extracellular matrix (ECM) has received extensive attention as a biomaterial due to its excellent biocompatibility and bioactivity. Among them, decellularized amniotic membrane (dAM) is of great interest due to its wide availability, easy accessibility, superior biocompatibility, fewer ethical issues, and low risk of pathogenic virus transmission compared to other allogeneic or xenogeneic decellularized matrices. dAM exhibits remarkable properties, including promoting epithelialization, reducing scarring, anti-inflammatory, and immunomodulatory effects. These properties are attributed to its unique composition and growth factors, such as epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF). Despite these advantages, pure dAM materials have limitations in mechanical properties, structural adjustability, reproducibility, and tissue-inducing activity, which cannot meet the demand for complex remodeling of ureteral tissue. To address these shortcomings, researchers have explored various methods to enhance the functionality of dAM. For example, a gelatin methacrylate (GelMA)-dAM composite hydrogel was found to accelerate tissue healing and promote skin wound regeneration. Sousa et al. modified dAM with methacrylic groups to create a multi-channel scaffold hydrogel, which showed significant effects in nerve repair, particularly in establishing functional synaptic connections. Liu et al. combined dAM with polycaprolactone (PCL) / silk fibroin (SF) through electrospinning to create an artificial blood vessel that reduced inflammation and immune rejection during a 24-week reconstruction process while maintaining patency. However, due to insufficient mechanical properties, these scaffolds face challenges when applied in situ for ureteral regeneration. Integrating dAM as a bioactive component into polymeric materials may meet the mechanical and bioactivity requirements of implants, and further research is needed to explore the role of dAM in ureter repair. SUMMARY
[0004] One advantage of the present invention is to provide a tubular porous scaffold integrating amniotic membrane and its preparation method and application. By integrating the enzymatically decellularized amniotic membrane (dAM) with silk fibroin and gelatin solution, a tubular porous scaffold (SGA) is prepared by freeze-drying, compression, and cross-linking method, providing a new treatment strategy for ureteral defect repair treatment, and opening up a new way for the development of urinary tissue engineering and the treatment of urinary tract diseases.
[0005] Another advantage of the present invention is to provide a tubular porous scaffold integrating amniotic membrane and its preparation method and application. By integrating the decellularized amniotic membrane hydrolyzed by pepsin into the tubular porous scaffold composed of gelatin and silk fibroin, the obtained tubular porous scaffold retains many functional properties of decellularized amniotic membrane, has the potential to promote scar-free ureter repair, and indicates that decellularized amniotic membrane has broad application prospects in regenerative medicine.
[0006] Another advantage of the present application is to provide a tubular porous scaffold integrated with amniotic membrane and a preparation method and application thereof, the prepared scaffold has high suturing strength, porous cross-sectional structure and dense surface structure, which is beneficial to the adhesion of epithelial cells, which is crucial for epithelial regeneration and tissue repair.
[0007] Another advantage of the present application is to provide a tubular porous scaffold integrated with amniotic membrane and a preparation method and application thereof, proteomic analysis shows that the SGA scaffold retains many functional properties of dAM, in vitro and in vivo experiments show that the SGA scaffold can enhance the epithelium of the urinary tract while inhibiting fibrosis, and successfully achieve scarless repair of partial ureteral defects in New Zealand rabbits.
[0008] Another advantage of the present application is to provide a tubular porous scaffold integrated with amniotic membrane and a preparation method and application thereof, the tubular porous scaffold integrated with amniotic membrane has no toxic side effects and has excellent blood compatibility.
[0009] Another advantage of the present application is to provide a tubular porous scaffold integrated with amniotic membrane and a preparation method and application thereof, the preparation method is simple, low in cost and good in clinical effect.
[0010] According to one aspect of the present application, the present application provides a preparation method of a tubular porous scaffold integrated with amniotic membrane, comprising the following steps: (S10) extracting fibroin from cocoon by lithium bromide dissolution method; (S20) preparing decellularized amniotic membrane by using detergent treatment and enzyme digestion; (S30) mixing fibroin and pigskin gelatin to prepare a fibroin / gelatin solution; and (S40) integrating the decellularized amniotic membrane with fibroin / gelatin to obtain a tubular porous scaffold integrated with amniotic membrane.
[0011] In the step (S20), the amniotic membrane is separated and sterilized, the sterilized amniotic membrane is first soaked in PBS containing 1% Triton X-100 to dissolve cells and nuclear membranes, and then lipids and nucleic acids are removed by enzyme to obtain the decellularized amniotic membrane, wherein the decellularized amniotic membrane is a white film.
[0012] In the step (S30), fibroin and pigskin-derived gelatin are mixed to prepare a 6.0% fibroin / gelatin solution at 60°C.
[0013] The mixing mass ratio of fibroin and pigskin-derived gelatin is 3:1-1:3.
[0014] The mixing mass ratio of fibroin and pigskin-derived gelatin is 3:1, 2:1, 1:1, 1:2 or 1:3.
[0015] The step (S10) comprises the following steps: (S101) removing sericin in the cocoon by using 0.5% sodium carbonate solution; (S102) washing and drying the obtained fibroin to obtain degummed fibroin; (S103) dissolving the degummed fibroin in a 9.3M lithium bromide solution and preparing a fibroin solution at 60°C; (S104) dialyzing the solution for three days to remove impurities; (S105) reverse dialyzing with a 10% PEG 20000 solution to obtain a fibroin solution with a concentration of 6.0%; and (S106) storing the obtained purified fibroin solution at 4°C.
[0016] The step (S40) comprises the following steps: (S401) freezing and freeze-drying the 6.0% fibroin / gelatin solution at -40°C; (S402) compressing the scaffold wall between two flat iron objects, and then treating with 95% ethanol and 1% glutaraldehyde respectively to induce crystallization and chemical crosslinking; (S403) obtaining decellularized amniotic membrane powder by treating the freeze-dried decellularized amniotic membrane with a low-temperature grinder; (S404) dissolving 500mg of the decellularized amniotic membrane powder in 10mL of a 5mg / mL pepsin solution, dissolving in 0.01M HCl, and then neutralizing with 0.1M NaOH; (S405) adding the 50mg / mL decellularized amniotic membrane solution to the scaffold and chemically crosslinking by EDC / NHS; and (S406) washing the scaffold with distilled water and freeze-drying.
[0017] In the step (S405), the mass ratio of dAM:EDC:NHS is 1:1:0.6.
[0018] According to another aspect of the present application, the present application also provides a tubular porous scaffold integrated with amniotic membrane, wherein the tubular porous scaffold integrated with amniotic membrane comprises decellularized amniotic membrane, gelatin and fibroin, and the tubular porous scaffold integrated with amniotic membrane is prepared by freeze-drying, compression and crosslinking.
[0019] According to another aspect of the present application, the present application also provides an application of the tubular porous scaffold integrated with amniotic membrane, wherein the tubular porous scaffold integrated with amniotic membrane has the functions of increasing uroepithelialization and inhibiting fibrosis, and is suitable for application in ureter scarless repair treatment, ureter defect repair treatment or ureter reconstruction. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 and Figure 2 is a schematic diagram of preparation and characterization of dAM.
[0021] Figure 3 is a schematic diagram of preparation of SGA scaffold.
[0022] Figure 4 andFigure 5 is a schematic representation of the characterization of SG, SGP and SGA scaffolds.
[0023] Figure 6 and Figure 7 is a schematic representation of the chemical composition analysis of the scaffolds.
[0024] Figure 8 , Figure 9 , Figure 10 , Figure 11 , Figure 12 and Figure 13 is a schematic representation of the protein assembly and release of SGA.
[0025] Figure 14 is a schematic representation of the hemocompatibility and hemolysis rate of all scaffolds.
[0026] Figure 15 , Figure 16 and Figure 17 is a schematic representation of the results of the effect of the scaffolds on the proliferation, morphology, degree of epithelialization and migration of the uroepithelial cells.
[0027] Figure 18 is a schematic representation of the results of the effect of the scaffolds on the transcriptional level of the degree of epithelialization of the UCs.
[0028] Figure 19 , Figure 20 and Figure 21 is a schematic representation of the results of the evaluation of the effect of the co-culture of SGA scaffolds on the proliferation, migration and differentiation of FBs. DETAILED DESCRIPTION
[0029] The following description is presented to enable any person skilled in the art to practice the application as claimed. The preferred embodiments disclosed herein are only examples of the application and alternative embodiments, modifications, improvements, equivalents, and the like can be made thereto without departing from the spirit and scope of the application as set forth in the following claims. The present application is defined by the claims.
[0030] In the present application, pepsin-hydrolyzed dAM was integrated into a tubular porous scaffold composed of gelatin and silk fibroin (SF) to evaluate its efficacy in ureteral defect repair. The dAM-integrated scaffold significantly promoted uroepithelial regeneration and early fibroblast differentiation into myofibroblasts. Notably, it also exhibited anti-fibrotic properties by suppressing excessive myofibroblast activation. Subsequent transcriptomic analysis revealed deeper insights into the underlying biological mechanisms. The present application aims to provide a new therapeutic approach for ureteral defect repair and theoretical support for the translational application of dAM in regenerative medicine, potentially driving the development of the field of urological tissue engineering.
[0031] The application provides a tubular porous scaffold integrated with amniotic membrane and a preparation method and application thereof. The prepared tubular porous scaffold integrated with amniotic membrane is prepared by integrating a solution of silk fibroin and gelatin with a decellularized amniotic membrane (dAM) through enzymatic hydrolysis, and a tubular porous scaffold (SGA) is prepared by using a freeze-drying, compression and cross-linking method. The SGA scaffold retains many functional properties of the dAM, can enhance uroepithelialization and inhibit fibrosis, and experiments show that the SGA scaffold has the potential to promote scar-free ureter repair, and is suitable for application in the treatment of ureter reconstruction.
[0032] The material sources and used equipment of the experiment are as follows: Hydroxysulfosuccinimide (NHS), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), sodium carbonate (AR) and lithium bromide (AR) are purchased from Aladdin (Shanghai, China). Pepsin (3000 U / g) and lipase are purchased from Solabio (Beijing, China). Mouse ureteral uroepithelial cells (UCs), fibroblasts (FBs) and all cell culture reagents are provided by Puresyn Biotechnology Co., Ltd. (Wuhan, China); TGF-β1 (Genescript, China); GP-transfect-Mate (GenePharma, China).
[0033] Amniotic membrane (AM) is provided by the First Affiliated Hospital of Ningbo University (ethics committee approval number: 2021B111). Pig skin-derived gelatin (Sigma-Aldrich, USA).
[0034] Freeze-drying equipment (Zirbus sublimator, Bad Grund, Germany); Fourier transform infrared spectroscopy (FTIR, Thermo, USA); Instron 3355 test system (Instron, USA); timsTOF Pro (Bruker, USA); UltiMate 3000 RSLCnano system (Thermo, USA); Costar transwell system (Corning, USA); scanning electron microscope (SEM, Phenom Scientific, Netherlands); atomic force microscope (AFM, Bruker, Germany); microplate reader (Bio-Rad, USA); Smad2 / 3 (Affinity, China); CT / CTU imaging (Toshiba, Japan); ex vivo micro-CT examination equipment (Pingseng Scientific, China); SP-5 laser scanning confocal microscope (LEIKA, Germany); (ELISA) kit (Kselisa, China); Total RNA Micro Kit (Magen Biotech, China); transcription kit (Takara, Japan). Example One
[0035] The preparation method of the amniotic membrane integrated tubular porous scaffold provided by the application comprises the following steps: (S10) Preparation of silk fibroin (SF); (S20) Preparation of decellularized amniotic membrane (dAM); (S30) Preparation of silk fibroin / gelatin (SG) solution; and (S40) Preparation of decellularized amniotic membrane integrated silk fibroin / gelatin (SGA) scaffold.
[0036] The scaffold is named according to the composition: SG (SF / gelatin), SGP (SF / gelatin / pepsin), SGA (SF / gelatin / pepsin / dAM), and SGAP (uncrosslinked SGA).
[0037] In the step (S10), the silk fibroin is extracted from the cocoon by using a lithium bromide dissolution method, comprising the following steps: (S101) The cocoon is cut into small pieces and boiled in a 0.5% sodium carbonate solution for 30 minutes, repeated three times, to remove sericin; (S102) The obtained silk fibroin is washed thoroughly with deionized water and dried to obtain degummed silk fibroin; (S103) The degummed silk fibroin is dissolved in a 9.3M lithium bromide solution to prepare a silk fibroin solution at 60°C; (S104) The solution was dialyzed for three days to remove lithium bromide and other impurities, and to improve purity; (S105) Reverse dialysis was performed using a 10% PEG 20000 solution to obtain a final 6.0% (w / v) silk fibroin solution; and (S106) The resulting purified SF solution remained stable for at least one week at 4°C without gelation, ready for use.
[0038] In the step (S20), the decellularization of the amniotic membrane (AM) comprises the following steps: (S201) Under sterile conditions, the fetal membrane was carefully separated from the placenta, and the blunt dissection technique was used to remove the villi and vascular tissue on the surface of the fetal membrane chorion, so as to maximize the integrity of the amniotic matrix; (S202) The separated amniotic membrane was oscillated in PBS containing antibiotics and antifungal agents for 24 hours to remove residual blood and impurities; (S203) After sterilization, the amniotic membrane was first soaked in PBS containing 1% Triton X-100 for 4 hours, which utilizes the surface active properties of this non-ionic detergent to dissolve cell and nuclear membranes, wherein Triton X-100 is polyethylene glycol octylphenyl ether; (S204) After washing with PBS, the sample was transferred to a PBS solution containing lipase (2000 U / L) and DNase (2000 U / L), and incubated at 37°C for 10 hours and 4 hours, respectively, to enzymatically remove lipids and nucleic acids; and (S205) The prepared dAM was stored at -80°C for subsequent experimental use.
[0039] It is worth mentioning that the above-mentioned decellularization process is crucial for the preparation of dAM, aiming to maximize the removal of cellular components while maintaining the natural structure and composition of ECM. The present application implements a two-step decellularization strategy involving detergent treatment and enzyme digestion to eliminate residual nucleic acids and lipids.
[0040] In the step (S30), silk fibroin (SF) and gelatin from pig skin are mixed to obtain a silk fibroin / gelatin solution (SG: SF / gelatin), wherein the mass ratio of silk fibroin (SF) and gelatin from pig skin is 4.5% SF / 1.5% gelatin (3:1).
[0041] In this embodiment, 6.0% (w / v) silk / gelatin and decellularized amniotic membrane were prepared at 60°C, and were placed in a polytetrafluoroethylene mold (inner diameter 2 mm) with a central stainless steel mandrel (diameter 1 mm) for compression crosslinking to obtain an SGA scaffold.
[0042] The step (S40) comprises the following steps: (S401) Freeze and lyophilize a 6.0% (w / v) silk fibroin / gelatin solution at -40°C to obtain an SG scaffold; (S402) Then treat with 95% ethanol and 1% glutaraldehyde for 30 minutes and 10 minutes, respectively, to induce crystallization and chemical crosslinking; (S403) Obtain dAM powder by treating lyophilized dAM using a cryogenic mill; (S404) Dissolve 500 mg of dAM powder in 10 mL of a 5 mg / mL pepsin solution, dissolve in 0.01M HCl for 1 day, and then neutralize with 0.1M NaOH; (S405) Add a 50 mg / mL dAM solution to the SG scaffold, compress the scaffold wall between two flat iron objects, and then chemically crosslink by EDC / NHS (mass ratio dAM:EDC:NHS = 1:1:0.6) for 24 hours, wherein the EDC / NHS crosslinking agent is a chemical reagent composed of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS); and (S406) Wash and lyophilize the obtained SGA scaffold with distilled water for 24 hours. Example Two
[0043] The preparation method of the amniotic membrane integrated tubular porous scaffold provided by the present application comprises the following steps: (S10) Preparation of silk fibroin (SF); (S20) Preparation of decellularized amniotic membrane (dAM); (S30) Preparation of silk fibroin / gelatin (SG) solution; and (S40) Preparation of decellularized amniotic membrane integrated silk fibroin / gelatin (SGA) scaffold.
[0044] The scaffold is named according to the composition: SG (SF / gelatin), SGP (SF / gelatin / pepsin), SGA (SF / gelatin / pepsin / dAM), and SGAP (uncrosslinked SGA).
[0045] In the step (S10), the silk fibroin is extracted from the cocoon by a lithium bromide dissolution method, comprising the following steps: (S101) Cut the cocoon into small pieces and boil in a 0.5% sodium carbonate solution for 30 minutes, repeated three times, to remove sericin; (S102) Thoroughly rinse and dry the obtained silk fibroin with deionized water to obtain degummed silk fibroin; (S103) Dissolve the degummed silk fibroin in 9.3 M lithium bromide solution to prepare a silk fibroin solution at 60 °C; (S104) Dialyze the solution for three days to remove lithium bromide and other impurities to improve purity; (S105) Reverse dialysis using 10% PEG 20000 solution to obtain a final 6.0% (w / v) silk fibroin solution; and (S106) The resulting purified SF solution is stable at 4 °C for at least one week without gelling for future use.
[0046] In the step (S20), the decellularization of the amniotic membrane (AM) includes the following steps: (S201) Under sterile conditions, carefully separate the fetal membrane from the placenta and remove the villi and vascular tissue on the surface of the fetal membrane chorion using blunt dissection techniques to maximize the integrity of the amniotic matrix; (S202) Shake the separated amniotic membrane in PBS containing antibiotics and antifungal agents for 24 hours to remove residual blood and impurities; (S203) After sterilization, the amniotic membrane is first soaked in PBS containing 1% Triton X-100 for 4 hours, taking advantage of the surface active properties of this non-ionic detergent to dissolve cell and nuclear membranes; (S204) After rinsing with PBS, the sample is transferred to a PBS solution containing lipase (2000 U / L) and DNase (2000 U / L) and incubated at 37 °C for 10 hours and 4 hours, respectively, to enzymatically remove lipids and nucleic acids; and (S205) The prepared dAM is stored at -80 °C for subsequent experimental use.
[0047] It is worth mentioning that the above-mentioned decellularization process is crucial for the preparation of dAM, aiming to maximize the removal of cellular components while maintaining the natural structure and composition of ECM. The present invention implements a two-step decellularization strategy involving detergent treatment and enzyme digestion to eliminate residual nucleic acids and lipids.
[0048] In the step (S30), silk fibroin (SF) and gelatin from pigskin are mixed to obtain a silk fibroin / gelatin solution (SG: SF / gelatin), wherein the mass ratio of silk fibroin (SF) and gelatin from pigskin is 4% SF / 2% gelatin (2:1).
[0049] In this embodiment, 6.0% (w / v) silk / gelatin and decellularized amniotic membrane are prepared at 60 °C and placed in a polytetrafluoroethylene mold (inner diameter 2 mm) with a central stainless steel mandrel (diameter 1 mm) for compression crosslinking to obtain an SGA scaffold.
[0050] The step (S40) comprises the following steps: (S401) Freeze and lyophilize a 6.0% (w / v) silk fibroin / gelatin solution at -40°C to obtain an SG scaffold; (S402) Then treat with 95% ethanol and 1% glutaraldehyde for 30 minutes and 10 minutes, respectively, to induce crystallization and water insolubility; (S403) Obtain dAM powder by treating lyophilized dAM using a cryogenic mill; (S404) Dissolve 500 mg of dAM powder in 10 mL of a 5 mg / mL pepsin solution, dissolve for 24 hours in 0.01M HCl, and then neutralize with 0.1M NaOH; (S405) Add a 50 mg / mL dAM solution to the SG scaffold, compress the scaffold wall between two flat iron objects, and then chemically crosslink by EDC / NHS (mass ratio dAM:EDC:NHS = 1:1:0.6) for 24 hours; and (S406) Wash and lyophilize the obtained SGA scaffold with distilled water for 24 hours. Example Three
[0051] The method for preparing the amniotic membrane-integrated tubular porous scaffold provided by the present application comprises the following steps: (S10) Preparation of silk fibroin (SF); (S20) Preparation of decellularized amniotic membrane (dAM); (S30) Preparation of silk fibroin / gelatin (SG) solution; and (S40) Preparation of decellularized amniotic membrane-integrated silk fibroin / gelatin (SGA) scaffold.
[0052] The scaffold is named according to the composition: SG (SF / gelatin), SGP (SF / gelatin / pepsin), SGA (SF / gelatin / pepsin / dAM), and SGAP (uncrosslinked SGA).
[0053] In the step (S10), the silk fibroin is extracted from silkworm cocoons by a lithium bromide dissolution method, comprising the following steps: (S101) Cut the silkworm cocoons into small pieces, and boil in a 0.5% sodium carbonate solution for 30 minutes, repeated three times, to remove sericin; (S102) Thoroughly rinse and dry the obtained silk fibroin with deionized water to obtain degummed silk fibroin; (S103) Dissolve the degummed silk fibroin in a 9.3M lithium bromide solution to prepare a silk fibroin solution at 60°C; (S104) The solution is dialyzed for three days to remove lithium bromide and other impurities to improve purity; (S105) Reverse dialysis is performed using a 10% PEG 20000 solution to obtain a final 6.0% (w / v) silk fibroin solution; and (S106) The resulting purified SF solution is stable at 4°C for at least one week without gelation, ready for use.
[0054] In the step (S20), the decellularization of the amniotic membrane (AM) includes the following steps: (S201) Under sterile conditions, the fetal membrane is carefully separated from the placenta, and the blunt dissection technique is used to remove the villi and vascular tissue on the surface of the fetal membrane chorion, so as to maximize the integrity of the amniotic matrix; (S202) The separated amniotic membrane is oscillated in PBS containing antibiotics and antifungal agents for 24 hours to remove residual blood and impurities; (S203) After sterilization, the amniotic membrane is first soaked in PBS containing 1% Triton X-100 for 4 hours, which utilizes the surface active properties of this non-ionic detergent to dissolve cell and nuclear membranes; (S204) After rinsing with PBS, the sample is transferred to a PBS solution containing lipase (2000 U / L) and DNase (2000 U / L), and incubated at 37°C for 10 hours and 4 hours, respectively, to enzymatically remove lipids and nucleic acids; and (S205) The prepared dAM is stored at -80°C for subsequent experimental use.
[0055] It is worth mentioning that the above-mentioned decellularization process is crucial for the preparation of dAM, aiming to maximize the removal of cellular components while maintaining the natural structure and composition of ECM. The present application implements a two-step decellularization strategy involving detergent treatment and enzyme digestion to eliminate residual nucleic acids and lipids.
[0056] In the step (S30), silk fibroin (SF) and gelatin from pigskin are mixed to obtain a silk fibroin / gelatin solution (SG: SF / gelatin), wherein the mixing ratio of silk fibroin (SF) and gelatin from pigskin is: 3% SF / 3% gelatin (1:1).
[0057] In this embodiment, 6.0% (w / v) silk / gelatin and decellularized amniotic membrane are prepared at 60°C, and are placed in a polytetrafluoroethylene mold (inner diameter 2 mm) with a central stainless steel mandrel (diameter 1 mm) for compression crosslinking to obtain an SGA scaffold.
[0058] The step (S40) includes the following steps: (S401) Freeze and lyophilize 6.0% (w / v) of silk fibroin / gelatin solution at -40°C to obtain SG scaffold; (S402) Then treat with 95% ethanol and 1% glutaraldehyde for 30 minutes and 10 minutes, respectively, to induce crystallization and chemical communication; (S403) Obtain dAM powder by treating lyophilized dAM using a cryogenic mill; (S404) Dissolve 500 mg of dAM powder in 10 mL of 5 mg / mL pepsin solution, dissolve in 0.01M HCl for 1 day, and then neutralize with 0.1M NaOH; (S405) Add 50 mg / mL dAM solution to the SG scaffold, compress the scaffold wall between two flat iron objects, and then chemically crosslink by EDC / NHS (mass ratio dAM:EDC:NHS = 1:1:0.6) for 24 hours; and (S406) The prepared SGA scaffold is washed with distilled water and lyophilized for 24 hours. Example Four
[0059] The preparation method of the amniotic membrane integrated tubular porous scaffold provided by the application comprises the following steps: (S10) Preparation of silk fibroin (SF); (S20) Preparation of decellularized amniotic membrane (dAM); (S30) Preparation of silk fibroin / gelatin (SG) solution; and (S40) Preparation of decellularized amniotic membrane integrated silk fibroin / gelatin (SGA) scaffold.
[0060] The scaffold is named according to the composition: SG (SF / gelatin), SGP (SF / gelatin / pepsin), SGA (SF / gelatin / pepsin / dAM), and SGAP (uncrosslinked SGA).
[0061] In the step (S10), the silk fibroin is extracted from the cocoon by using lithium bromide dissolution method, which comprises the following steps: (S101) Cut the cocoon into small pieces and boil in 0.5% sodium carbonate solution for 30 minutes, repeat three times to remove sericin; (S102) Thoroughly rinse the obtained silk fibroin with deionized water and dry to obtain degummed silk fibroin; (S103) Dissolve the degummed silk fibroin in 9.3M lithium bromide solution to prepare a silk fibroin solution at 60°C; (S104) Dialyze the solution for three days to remove lithium bromide and other impurities to improve purity; (S105) Reverse dialysis using 10% PEG 20000 solution to obtain a final 6.0% (w / v) silk fibroin solution; and (S106) The obtained purified SF solution is stable at 4°C for at least one week without gelation, ready for use.
[0062] In the step (S20), the decellularization of the amniotic membrane (AM) comprises the following steps: (S201) Under sterile conditions, the fetal membrane is carefully separated from the placenta, and the blunt dissection technique is used to remove the villi and vascular tissue on the surface of the fetal membrane chorion, so as to maximize the integrity of the amniotic matrix; (S202) The separated amniotic membrane is oscillated in PBS containing antibiotics and antifungal agents for 24 hours to remove residual blood and impurities; (S203) The sterilized amniotic membrane is first soaked in PBS containing 1% Triton X-100 for 4 hours, and the surface active properties of this non-ionic detergent are used to dissolve the cell and nuclear membranes; (S204) After washing with PBS, the sample is transferred to a PBS solution containing lipase (2000 U / L) and DNase (2000 U / L), and incubated at 37°C for 10 hours and 4 hours, respectively, to enzymatically remove lipids and nucleic acids; and (S205) The prepared dAM is stored at -80°C for subsequent experimental use.
[0063] It is worth mentioning that the above-mentioned decellularization process is crucial for the preparation of dAM, aiming to maximize the removal of cellular components while maintaining the natural structure and composition of ECM. The present application implements a two-step decellularization strategy involving detergent treatment and enzyme digestion to eliminate residual nucleic acids and lipids.
[0064] In the step (S30), silk fibroin (SF) and gelatin from pigskin are mixed to obtain a silk fibroin / gelatin solution (SG: SF / gelatin), wherein the mixing ratio of silk fibroin (SF) and gelatin from pigskin is: 2% SF / 4% gelatin (1:2).
[0065] In this embodiment, 6.0% (w / v) silk / gelatin and decellularized amniotic membrane are prepared at 60°C, and are placed in a polytetrafluoroethylene mold (inner diameter 2 mm) with a central stainless steel mandrel (diameter 1 mm) for compression crosslinking to obtain an SGA scaffold.
[0066] The step (S40) comprises the following steps: (S401) Freeze and lyophilize the 6.0% (w / v) silk / gelatin solution at -40°C to obtain an SG scaffold; (S402) Then, 95% ethanol and 1% glutaraldehyde were used to treat for 30 minutes and 10 minutes, respectively, to induce crystallization and chemical cross-linking; (S403) dAM powder was obtained by treating the freeze-dried dAM using a cryomill; (S404) 500 mg of dAM powder was dissolved in 10 mL of a 5 mg / mL pepsin solution, dissolved in 0.01 M HCl for 1 day, and then neutralized with 0.1 M NaOH; (S405) A 50 mg / mL dAM solution was added to the SG scaffold, the scaffold wall was compressed between two flat iron objects, and then chemical cross-linking was performed by EDC / NHS (mass ratio dAM:EDC:NHS = 1:1:0.6) for 24 hours; and (S406) The obtained SGA scaffold was washed with distilled water and freeze-dried for 24 hours. Example Five
[0067] The preparation method of the amniotic membrane integrated tubular porous scaffold provided by the present application comprises the following steps: (S10) Preparation of silk fibroin (SF); (S20) Preparation of decellularized amniotic membrane (dAM); (S30) Preparation of silk fibroin / gelatin (SG) solution; and (S40) Preparation of decellularized amniotic membrane integrated silk fibroin / gelatin (SGA) scaffold.
[0068] The scaffold is named according to the composition: SG (SF / gelatin), SGP (SF / gelatin / pepsin), SGA (SF / gelatin / pepsin / dAM), and SGAP (uncross-linked SGA).
[0069] In the step (S10), the silk fibroin is extracted from the cocoon by using a lithium bromide dissolution method, comprising the following steps: (S101) The cocoon is cut into small pieces and boiled in a 0.5% sodium carbonate solution for 30 minutes, repeated three times, to remove sericin; (S102) The obtained silk fibroin is thoroughly washed with deionized water and dried to obtain degummed silk fibroin; (S103) The degummed silk fibroin is dissolved in a 9.3 M lithium bromide solution to prepare a silk fibroin solution at 60°C; (S104) The solution is dialyzed for three days to remove lithium bromide and other impurities to improve purity; (S105) Reverse dialysis is performed using a 10% PEG 20000 solution to obtain a final 6.0% (w / v) silk fibroin solution; and (S106) The obtained purified SF solution is stable at 4°C for at least one week without gelling, ready for use.
[0070] In the step (S20), the decellularization of the amniotic membrane (AM) comprises the following steps: (S201) Under sterile conditions, the fetal membrane is carefully separated from the placenta, and the blunt dissection technique is used to remove the villi and vascular tissue on the surface of the fetal membrane chorion, so as to maximize the integrity of the amniotic matrix; (S202) The separated amniotic membrane is oscillated in PBS containing antibiotics and antifungal agents for 24 hours to remove residual blood and impurities; (S203) The disinfected amniotic membrane is first soaked in PBS containing 1% Triton X-100 for 4 hours, and the surface active properties of this non-ionic detergent are used to dissolve the cell and nuclear membranes; (S204) After washing with PBS, the sample is transferred to a PBS solution containing lipase (2000 U / L) and DNase (2000 U / L), and incubated at 37°C for 10 hours and 4 hours, respectively, to enzymatically remove lipids and nucleic acids; and (S205) The prepared dAM is stored at -80°C for subsequent experimental use.
[0071] It is worth mentioning that the above-mentioned decellularization process is crucial for the preparation of dAM, aiming to maximize the removal of cellular components while maintaining the natural structure and composition of ECM. The present application implements a two-step decellularization strategy involving detergent treatment and enzyme digestion to eliminate residual nucleic acids and lipids.
[0072] In the step (S30), the silk fibroin (SF) and the gelatin derived from pigskin are mixed to obtain a silk fibroin / gelatin solution (SG: SF / gelatin), wherein the mixing ratio of silk fibroin (SF) and gelatin derived from pigskin is: 1.5% SF / 4.5% gelatin (1:3).
[0073] In this embodiment, 6.0% (w / v) silk / gelatin and decellularized amniotic membrane are prepared at 60°C, and are placed in a polytetrafluoroethylene mold (inner diameter 2 mm) with a central stainless steel mandrel (diameter 1 mm) for compression crosslinking to obtain an SGA scaffold.
[0074] The step (S40) comprises the following steps: (S401) Freeze and lyophilize the 6.0% (w / v) silk / gelatin solution at -40°C to obtain an SG scaffold; (S402) Then treat with 95% ethanol and 1% glutaraldehyde for 30 minutes and 10 minutes, respectively, to induce crystallization and chemical crosslinking; (S403) dAM powder was obtained by treating freeze-dried dAM using a cryogenic mill; (S404) 500 mg of dAM powder was dissolved in 10 mL of 5 mg / mL pepsin solution, dissolved in 0.01 M HCl for 1 day, and then neutralized with 0.1 M NaOH; (S405) 50 mg / mL dAM solution was added to the SG scaffold, the scaffold wall was compressed between two flat iron objects, and then chemically cross-linked by EDC / NHS (mass ratio dAM: EDC: NHS = 1: 1: 0.6) for 24 hours; and (S406) The obtained SGA scaffold was washed with distilled water and freeze-dried for 24 hours.
[0075] The following functional verification experiments used materials prepared by Example One, wherein the characterization and biological detection of the SGA scaffold are as follows: Characterization of SGA scaffold: The mechanical properties of the scaffold were evaluated using an Instron 3355 testing system (Instron, USA). The morphology, roughness, elemental composition, and wettability were measured, respectively.
[0076] Longitudinal strips (20 mm x 5 mm) were prepared and stretched to break at a speed of 1 mm / min. For suture retention strength testing, the sample was punctured with an 8-0 absorbable suture (China Jinhuang) at 1 mm from the edge, and stretched at a speed of 1 mm / min until the suture pulled out or the sample broke.
[0077] In order to verify whether the decellularized amniotic membrane (dAM) is successfully integrated into the scaffold, the present application conducts Fourier transform infrared spectroscopy analysis.
[0078] The scaffold sample was cut into small pieces, and equal amounts of dAM and pepsin powder were used as controls. The samples were placed on an attenuated total reflection (ATR) accessory, and the spectral signals were collected using an infrared spectrometer. The scanning wave number range was 500-4000 cm -1 By comparing the characteristic absorption peaks of each group, it was determined whether the dAM was integrated into the scaffold.
[0079] The internal surface and cross-sectional morphology of the scaffolds were observed using a scanning electron microscope. For cross-sectional information, the scaffold samples were snap-frozen in liquid nitrogen until brittle. The fractured surface was gold-coated under vacuum and placed on the SEM sample stage. Images were taken at an acceleration voltage of 10 kV. In addition, the EDS function of the SEM was used to analyze the elemental composition and distribution of the SGA scaffold surface. The internal surface of the scaffold sample was prepared for SEM analysis. Characteristic X-ray signals of C, N, and O elements were collected at an acceleration voltage of 10 kV, an electron beam current of 6.0, and a working distance of 9.0 mm.
[0080] The internal surface of the scaffolds was observed using an atomic force microscope and its roughness was measured. After sample preparation, the scaffolds were placed on the AFM platform with the following parameters: probe type ScanAsyst-Air, scanning mode ScanAsyst in Air, scanning frequency 1 Hz, scanning area 5 pm. The obtained raw data were analyzed using Nanoscope Analysis software.
[0081] The change in surface hydrophilicity was evaluated using a contact angle measuring device (Thermo). The scaffold samples were placed in a vacuum oven at 37 °C overnight to remove surface moisture. A drop of deionized water was dropped on the internal surface of the scaffold and allowed to spread for 10 seconds. The shape of the water droplet on the scaffold surface was photographed, and the contact angle was measured using image analysis software.
[0082] Protein assay of the scaffolds: The testing method of protein lysate of dAM and SGA scaffolds was as follows: tris(2-carboxyethyl)phosphine and chloroacetamide were added for protein reduction alkylation reaction, and incubated at 37 °C for 1 hour. After trypsin digestion, all samples were analyzed on a timsTOF Pro, which is a hybrid trapped ion mobility spectrometry quadrupole time-of-flight mass spectrometer. The UltiMate 3000 RSLCnano system was coupled to the CaptiveSpray nanoelectrospray ion source to the timsTOF Pro. The DIA raw data files were analyzed by DIA-NN software (v 1.8, UK). The human proteome reference database in Uniprot (20,377 protein sequences) was used. The results were analyzed by gene ontology and Kyoto Encyclopedia of Genes and Genomes to screen for relevant targets.
[0083] Collagen and growth factors were analyzed by immunofluorescence (IF) and enzyme-linked immunosorbent assay (ELISA).
[0084] Scaffolds were fixed in 10% buffered formalin, dehydrated and embedded in paraffin. Sections (6 pm) were stained with Masson's trichrome staining to detect collagen and immunostained with anti-bFGF (Proteintech, 1 :500) and anti-EGF (Proteintech, 1 :500) antibodies. Fluorescent secondary antibodies (Proteintech, 1 : 1000) were used and visualized under a SP-5 laser scanning confocal microscope.
[0085] Endogenous bFGF and EGF in dAM, SGA and SGAP scaffolds were quantitatively detected using enzyme-linked immunosorbent assay (ELISA) kits. Scaffolds were placed in 3.0 mL PBS and shaken at 200 rpm. At predetermined time points, extraction buffer was collected and replaced with fresh PBS. Growth factor concentrations were calculated using a standard curve, and release curves were estimated according to the corresponding concentrations.
[0086] In vitro cell experiments: Cell proliferation was quantitatively evaluated using a CCK-8 kit at day 1, day 3 and day 5. Scaffolds-induced cell migration was evaluated by wound healing experiments. Transwell migration experiments were performed using a Costar transwell system to test scaffolds-induced fibroblast migration. The levels of urothelialization and myofibroblast-like differentiation were detected by immunofluorescence (IF) and quantitative real-time polymerase chain reaction (qRT-PCR), primer sequences and nucleotide sequences are shown in Table 1 and Table 2.
[0087]
[0088]
[0089] Specifically, in CCK-8 detection, UCs on scaffolds or FBs co-cultured with scaffolds were incubated with 10% CCK-8 reagent at 37°C for 2 hours. Absorbance at 450 nm was measured using a microplate reader. For SEM observation, adherent UCs were fixed with 2.5% glutaraldehyde, dehydrated with gradient ethanol, and gold-coated before observation.
[0090] In wound healing experiments, cells were seeded in six-well plates at a density of 1 x 10 5 cells / well. When cells reached 80-90% confluence, a 200 pL pipette tip was used to scratch. After PBS washing, scaffold extracts were added to the wells. Three representative images of the scratch area were taken, and cell migration was evaluated using ImageJ software.
[0091] In Transwell migration experiments, scaffolds were added to the lower chamber, while 100 pL of FB suspension (1 x 10 5The cells were seeded in the upper chamber. After 8 hours of incubation, non-migrated FBs were removed and migrated cells were stained with crystal violet and observed under a microscope.
[0092] IF staining with ZO-1 and UPK III was used to assess UCs on the scaffold for uroepithelialization, while a-SMA staining visualized myofibroblast-like differentiation of FBs co-cultured with the scaffold b-actin as an internal control. Relative quantification was performed using ImageJ software.
[0093] Gene expression levels were measured by quantitative real-time polymerase chain reaction (qRT-PCR). RNA was extracted using the Total RNA MicroKit and transcribed into cDNA using the Transcription Kit. mRNA levels were quantified using the SYBR Green PCR Kit, and data were presented as relative quantification (2-ACt) compared to the control group.
[0094] Ureteral repair experiments and imaging analysis: New Zealand rabbits were repaired with a 3 cm ureteral defect using a scaffold as a negative control, while autologous ureteral suture was used as a positive control (Ctrl group). Animals were sacrificed at 2 weeks and 3 months postoperatively for histological examination. The patency of the upper urinary tract and ureteral tissue was evaluated by in vivo computed tomography (CT) / urography (CTU) and ex vivo micro-CT. Blood samples were collected from the inferior vena cava for serum analysis. Blood urea nitrogen (BUN) and creatinine (Cr) concentrations were measured to assess renal function. The procedures were as follows: New Zealand rabbits were fasted for 12 hours before surgery and anesthetized by ear vein injection. Under sterile conditions, the abdomen was opened along the midline to access the abdominal cavity. The right ureter was isolated, and a 3 cm segment was excised to create a defect model.
[0095] The scaffold was placed at the defect site and anastomosed to the proximal and distal ureteral ends using 8-0 absorbable sutures under a microscope, ensuring tension-free and twist-free anastomosis. For the autologous transplantation control, the excised ureter was reimplanted. A 3Fr ureteral stent was inserted to prevent leakage. The anastomotic site was wrapped with omentum to reduce the risk of urine leakage. The abdominal wall and skin were layered sutured.
[0096] Two weeks after surgery, the rabbits were re-anesthetized, and the ureteral stent was removed through a bladder incision. At 2 weeks and 3 months postoperatively, the rabbits were sacrificed, and the grafted ureteral segments were collected. The samples were fixed in 4% paraformaldehyde, embedded in paraffin, sectioned, and stained with HE and Masson's trichrome for histological analysis.
[0097] At 3 months postoperatively, New Zealand rabbits underwent CT / CTU imaging to assess ureteral patency and hydronephrosis. Rabbits were sedated by ear vein injection of a 5% solution of pentobarbital (5 mL / kg) and placed supine on the CT scanner bed. Abdominal plain scan images were acquired to assess kidney morphology and ureteral course. Then, iodine contrast was injected intravenously slowly. CT scans were performed immediately after injection and at 5, 15, and 30 minutes to obtain time-staged urographic images. Ureteral patency and pyelographic visualization were analyzed according to CT value changes. DICOM images were processed using Vitrea Fx 4.0 software on a Toshiba 320 CT workstation. Three-dimensional ureteral images were generated using multiplanar reconstruction (MPR), maximum intensity projection (MIP), and volume rendering (VR) techniques. Graft patency and healing were assessed according to luminal continuity, degree of stenosis, and dilatation. Anteroposterior diameters of the renal pelvis and ureter were measured to assess the severity of hydronephrosis.
[0098] In addition, excised ureteral segments were subjected to ex vivo micro-CT examination at 3 months postoperatively to visualize luminal stenosis and tissue hyperplasia.
[0099] Results analysis of the above experiments of the present application 1. Characterization of dAM The preparation and characterization results of dAM are shown in Figure 1 and Figure 2 , wherein Figure 1 (A) is the general photograph of AM and dAM; (B) is the DNA quantification of non-decellularized and decellularized AM; (C) is the HE staining, SEM image and DAPI staining of AM and dAM, with black arrows pointing to epithelial cells; Figure 2 is the EGF and bFGF release of AM and dAM. Data are expressed as mean ± standard deviation (*p<0.05, **p<0.01, ****p<0.0001).
[0100] As can be seen from the quantitative analysis in (B) of Figure 1 , the DNA content in dAM is significantly reduced (p<0.0001).
[0101] As can be seen from (A) of Figure 1 , fresh amniotic membrane (AM) is translucent and smooth on the surface, while the decellularized amniotic membrane (dAM) after treatment becomes a white film.
[0102] As can be seen from Figure 1From Figure 2 (C), scanning electron microscope (SEM) analysis showed that the intact epithelial layer of AM was removed in dAM, exposing the collagen fiber network (as shown in SEM); HE staining confirmed the stratified structure of AM with columnar urothel, while dAM only exhibited a loose matrix network (as shown in HE). These findings were confirmed by DAPI staining (as shown in DAPI).
[0103] From Figure 2 ELISA detection showed that the level of EGF remained unchanged in dAM compared to AM, while the level of bFGF was slightly reduced, indicating successful cell removal while retaining growth factors. The retention of these growth factors is crucial because EGF and bFGF play an important role in tissue repair, particularly in promoting epithelialization and urological regeneration.
[0104] 2. Ureteral stent characterization The mechanical properties of the stent were significantly affected by the ratio of SF to gelatin. The synthesis and characterization of the stent are shown in Figure 3 and Figure 4 , Figure 5 wherein Figure 3 is a schematic diagram of SGA stent preparation; Figure 4 (A) of Figure 2 is the stress-strain curve of stents with different SF and gelatin ratios, with the corresponding breaking stress and strain marked beside the curve; Figure 5 (A) of Figure 3 is the microstructure of SG, SGP, and SGA stents observed by SEM; Figure 4 (B) of Figure 3 is the roughness (Ra) map using AFM images; Figure 5 (B) of Figure 4 is the suturing strength of SG, SGP, and SGA stents; Figure 5 (C) of Figure 4 is the contact angle. Data are presented as mean ± standard deviation (ns: p>0.05, **p<0.01) From Figure 4 the stress-strain curve of (B) of Figure 2, increasing the SF content increases the strength but decreases the ductility, which is attributed to the β-sheet structure in SF molecules that enhances rigidity. In contrast, a higher gelatin content results in lower breaking stress but slightly higher breaking strain due to the random coil structure of gelatin. The mass ratio of 1:1 SF to gelatin was chosen as the optimal ratio, resulting in a breaking stress of 0.75 MPa and a strain of 83.34%.
[0105] The structure and hydrophilicity of the stent play a key role in urothelial regeneration and tissue repair. From Figure 5 (A) of Figure 5 SEM observation showed that the stent had a loose, porous internal structure and a dense surface structure, which was conducive to nutrient exchange and cell growth. Compression treatment resulted in a flat pore, forming a dense non-porous inner wall layer, which was conducive to the adhesion of epithelial cells.
[0106] From Figure 4 (B) of FIG. 1, AFM analysis showed that the inner wall surface roughness of the scaffolds was similar (p>0.05).
[0107] From Figure 5 (B) of FIG. 1, suture strength test showed that the strength of all scaffolds reached the level of megapascal, meeting the mechanical requirements of ureter repair.
[0108] From Figure 5 (C) of FIG. 1, water contact angle measurement showed that the angle of SGA scaffold was significantly lower than that of SG and SGP scaffolds (55.14±4.32°) (p<0.01), which may be due to the hydrophilic groups in dAM.
[0109] Figure 6 FIG. 1 is a schematic diagram of the chemical composition analysis results of the scaffold, wherein (A) is the FTIR spectrum of pepsinase, dAM, SG, SGP, and SGA; (B) is the EDS spectrum of SGA scaffold and the proportion of C, N, and O.
[0110] Figure 7 FIG. 2 is a schematic diagram of the composition analysis results of the scaffold, wherein (A) is the energy dispersive spectrum (EDS) of SG, SGP, and SGA; (B) and (C) are the Masson staining diagrams of SG and SGP, respectively.
[0111] Figure 8 to Figure 13 FIG. 3 is a schematic diagram of the results of protein assembly and release of SGA, wherein Figure 8 and Figure 9 are protein analysis of dAM and SGA: the number of overlapping proteins is analyzed by Venn diagram; the correlation between the two is analyzed by scatter plot; Figure 10 is a pie chart of overlapping protein composition analysis. Figure 11 is GO and KEGG pathway enrichment analysis and functional annotation of overlapping proteins; Figure 12 (A) of FIG. 4 is the Western blot band of Col1A, CD44, CD9, TGF-β1, and WNT11 in dAM and SGA; Figure 12 (B) of FIG. 4 is the Masson and IF staining of SGA, which respectively shows as Figure 13 (A) bFGF and (B) EGF in FIG. 5; (C) is the EGF release curve of dAM, SGAS, and SGA; (D) is the bFGF release curve.
[0112] From Figure 6 (A) of FIG. 6, the FTIR results of SGA scaffold showed characteristic peaks at 3390 cm -1 and 1737 cm -1 , representing the stretching vibration of amino / hydroxyl and ester carbonyl, respectively.
[0113] From Figure 7 EDS spectra of all scaffolds, it can be seen that the C, N and O element compositions of all scaffolds are consistent, and as shown in Figure 9 , the mass fractions of SGA scaffold are 47.24%, 21.70% and 31.06% respectively.
[0114] 3. Mass spectrometry analysis and protein function research In order to accurately characterize the dAM incorporated in the SGA scaffold, the present application also carries out mass spectrometry and proteomics analysis, and compares it with pure dAM. The results show that, as shown in Figure 8 , SGA scaffold and dAM share 74.8% (4080 kinds) of proteins, and the integration rate is 75.58%; as shown in Figure 9 , the protein expression levels between the two show a strong linear relationship, indicating that the SGA scaffold successfully retains the main protein components of dAM.
[0115] As shown in Figure 10 , the functional analysis of the common proteins shows that they are involved in local adhesion, tight junction, motor protein, adherens junction and ECM-receptor interaction processes, which indicates that they play a key role in regulating cell behavior and tissue repair microenvironment. As shown in Figure 11 , GO and KEGG enrichment analysis highlights significant enrichment in biological processes such as injury repair, cell development, cytoskeleton reconstruction, cell-cell junction, epithelialization, ECM remodeling and cell adhesion. As shown in Figure 12 (A), WB confirms the presence of key proteins related to cell adhesion, epithelialization and tissue regeneration in SGA scaffold, including Col 1A related to local adhesion, CD44 and CD9 related to epithelialization and tight junction, TGF-β1 involved in ECM-related biological processes, and WNT11 related to injury repair and cell development. These proteins may act as core driving factors for scarless ureter repair, highlighting the comprehensive biological activity characteristics of SGA scaffold.
[0116] As shown in Figure 7 (B), (C) and Figure 12 (B), Masson trichrome staining shows that there is obvious blue collagen in the SGA scaffold compared with the SG and SGP scaffolds. As shown in Figure 13 (A), (B), IF confirms the presence of bFGF and EGF in SGA. As shown in Figure 13The SGA scaffold showed sustained release of these growth factors, with EGF and bFGF release lasting 7 and 11 days, respectively, as shown in Figures (C), (D) in the Results section. This extended release profile is particularly important because many growth factors exert their primary effects during the proliferative phase, which typically occurs at least 3 days after the initial inflammatory phase. The sustained release profile of the SGA scaffold can stimulate endogenous tissue regeneration and promote ureteral repair after implantation, providing a sustained supportive environment for tissue healing and remodeling.
[0117] 4. Cell compatibility experiments The biocompatibility and cell interaction of the scaffolds were extensively evaluated. The results are shown in Figure 14 to Figure 21
[0118] Figure 14 The blood compatibility and hemolysis rate of all scaffolds are shown.
[0119] Figure 15 to Figure 17 The effects of the scaffolds on the proliferation, morphology, epithelialization degree, and migration of uroepithelial cells. Figure 15 Figure (A) in the Results section shows the cell proliferation of UCs on different scaffolds at 1 day, 3 days, and 5 days as detected by CCK-8; Figure 15 Figure (B) in the Results section shows the AE1 / AE3 (green) and F-actin (red) immunofluorescence of UCs on scaffolds at 3 days and 5 days, with DAPI used for staining the cell nuclei; Figure 16 Figure (A) in the Results section shows SEM images of the morphology of UCs on scaffolds; Figure 16 Figures (B) and (C) in the Results section show the expression of ZO-1 and UP III (green), respectively, using confocal fluorescence microscopy, with β-actin (red) used as an internal reference and DAPI used for staining the cell nuclei; Figure 17 Figure (A) in the Results section shows the Figure 16 Figures (B) and (C) in the Results section show the semi-quantitative analysis of fluorescence intensity, which shows that ZO-1 and UP III in UCs on the SGA scaffold were significantly increased compared to other scaffolds; Figure 17 Figures (B), (C) in the Results section show dark-field images and statistical data of UCs cultured with different scaffold extracts in the wound healing experiment, with the acellular area measured by ImageJ software. The data are presented as mean ± standard deviation (ns: p>0.05, *p<0.05, **p<0.01, ***p<0.001).
[0120] Figure 18 To evaluate the effect of the scaffolds on the transcriptional level of UCs epithelialization, (A) is the agarose gel electrophoresis band of RT-PCR amplification products of UCs on scaffolds, using ZO-1 and UP III specific primers to quantify the corresponding mRNA transcription, GAPDH primers were used as internal control; (B) is the qRT-PCR analysis of the relative mRNA expression level of ZO-1 and UP III genes of UCs on different scaffolds. Data are expressed as mean ± standard deviation (**p<0.01, ***p<0.001).
[0121] Figure 19 to Figure 21 To evaluate the effect of the scaffolds on the transcriptional level of UCs epithelialization, (A) is the agarose gel electrophoresis band of RT-PCR amplification products of UCs on scaffolds, using ZO-1 and UP III specific primers to quantify the corresponding mRNA transcription, GAPDH primers were used as internal control; (B) is the qRT-PCR analysis of the relative mRNA expression level of ZO-1 and UP III genes of UCs on different scaffolds. Data are expressed as mean ± standard deviation (**p<0.01, ***p<0.001). Figure 19 (A), (B) are the migration of FBs cultured in different scaffold extracts analyzed using scratch test and Transwell test. Figure 20 (A) is the cell proliferation of FBs at 1 day, 3 days and 5 days detected by CCK-8 with different scaffold extracts; (B), (C) are the semi-quantitative analysis of scratch test and Transwell test; (D) is the semi-quantitative analysis of F-actin and α-SMA immunofluorescence. Figure 21 To evaluate the level of myofibroblast differentiation of FBs in different extracts using immunofluorescence. Data are expressed as mean ± standard deviation (*p<0.05, **p<0.01, ***p<0.001, ****p<0.0001).
[0122] As shown in the hemolysis test in Figure 14 , the hemolysis rate of all three scaffolds is less than 5%, indicating that they have excellent blood compatibility.
[0123] The present application also evaluates the effect of the scaffolds on the epithelialization of uroepithelial cells (UCs). As shown in (A) CCK-8 assay in Figure 15 , all scaffolds support the adhesion and proliferation of UCs, among which the SGA scaffold shows significantly higher number of UCs at day 3 and day 5 (p<0.05), which indicates that the SGA scaffold may contain more bioactive substances (such as EGF) to promote the growth of UCs, which is consistent with the results of early material characterization.
[0124] As shown in (B) IF analysis in Figure 15 , UCs maintain the characteristic epithelial phenotype markers (AE1 / AE3, green) and intact cytoskeleton (F-actin, red) on all scaffolds, indicating that no abnormal differentiation or dedifferentiation is induced by the scaffolds. As shown in Figure 16SEM observations in (A) showed that UCs were tightly packed on the scaffold surface, and the SGA scaffold promoted multilayered growth similar to the natural urothelial structure. Since UCs form the innermost layer directly facing the urine, they play a crucial role in urothelialization, preventing harmful urinary components from entering the subepithelial layer. Tight junctions and the formation of asymmetric unit membranes are essential in this process; UCs cultured on the SGA scaffold expressed higher levels of ZO-1 and UP III, such as... Figure 16 (B), (C) and Figure 17 As shown in (A), these represent more mature tightly connected and asymmetric unit membranes, respectively.
[0125] like Figure 18 As shown, RT-PCR and qRT-PCR analyses confirmed that the mRNA expression of these genes was higher in the SGA group (p<0.01).
[0126] In addition, such as Figure 17 Images (B) and (C) show that the SGA scaffold significantly enhanced UC migration after 72 hours of co-culture (p<0.05). This may be due to migration factors or regulatory molecules released by the SGA scaffold. These combined findings highlight the superior ability of the SGA scaffold to promote functional urothelialization, a key aspect of successful ureteral repair.
[0127] This invention also investigated the effects of the scaffold on fibroblasts (BFs). Figure 19 (A) and Figure 20 As shown in (B) of the diagram, the scratch test revealed that the SGA group had significantly larger BFs migration areas at 12 and 24 hours (p<0.05, p<0.01). Figure 19 (B) and Figure 20 The (C) Transwell experiment showed that the SGA group exhibited higher invasiveness of BFs after 12 hours of co-culture (p<0.001). Figure 20 As shown in (A), CCK-8 assays revealed enhanced BF proliferation in the SGA group, particularly on days 3 and 5 (p<0.001, p<0.0001). Figure 21 And such as Figure 20 (D) Relative fluorescence intensity (IF) observation of each cell showed that the BFs cytoskeleton after 3 days of co-culture exhibited a distinct non-reticular structure in the SGA group, with increased F-actin intensity (p<0.01), indicating possible myofibroblast differentiation. Furthermore, myofibroblasts were assessed by α-SMA staining, and the results showed that the SGA group had a higher α-SMA positive area and fluorescence intensity (p<0.0001), indicating enhanced myofibroblast differentiation.
[0128] In summary, the dAM integrated SGA scaffold suitable for ureteral defect repair is successfully developed by a simple freeze-drying, compression and cross-linking method. The scaffold effectively promotes the regeneration of uroepithelium and the anti-fibrosis characteristics, and promotes the scar-free healing of ureter. Therefore, the present application provides a new ureteral defect repair treatment strategy, and provides theoretical support for the transformation application of dAM in regenerative medicine. It has important significance for promoting the development of urological tissue engineering, and opens up a new way for the treatment of urinary tract diseases.
[0129] It will be understood by those skilled in the art that the above-described embodiments of the present application shown in the description and drawings are only as examples and do not limit the present application. The purpose of the present application has been fully and effectively achieved. The function and structural principle of the present application has been shown and explained in the embodiments, and the implementation of the present application can have any modification or modification without departing from the principle.
Claims
1. A method for preparing a tubular porous scaffold integrating amnion, characterized in that, Includes the following steps: (S10) Silk fibroin was extracted from silkworm cocoons using the lithium bromide dissolution method; (S20) Decellularized amnion was prepared by detergent treatment and enzyme digestion; (S30) Prepare a silk fibroin / gelatin solution by mixing silk fibroin and gelatin derived from pigskin; as well as (S40) The decellularized amnion is integrated into the silk fibroin / gelatin scaffold by compression cross-linking to obtain a tubular porous scaffold with integrated amnion.
2. The method for preparing a tubular porous scaffold with integrated amnion according to claim 1, wherein in step (S20), the amnion is separated and sterilized, soaked in a non-ionic detergent to dissolve cells and nuclear membranes, and then lipids and nucleic acids are enzymatically removed to obtain a decellularized amnion, wherein the decellularized amnion is a white film.
3. The method for preparing the tubular porous scaffold with integrated amnion according to claim 2, wherein in step (S20), the nonionic detergent is a PBS solution containing 1% Triton X-100.
4. The method for preparing the tubular porous scaffold with integrated amnion according to claim 2, wherein the mass ratio of silk fibroin and porcine gelatin is 3:1-1:
3.
5. The method for preparing the tubular porous scaffold with integrated amnion according to claim 4, wherein in step (S30), the mixing mass ratio of silk fibroin and porcine gelatin is 3:1, 2:1, 1:1, 1:2 or 1:
3.
6. The method for preparing a tubular porous scaffold with integrated amnion according to any one of claims 1 to 5, wherein step (S10) comprises the following steps: (S101) Use 0.5% sodium carbonate solution to remove sericin from silkworm cocoons; (S102) Wash and dry the obtained sericin to obtain degummed sericin; (S103) Dissolve the degummed sericin in 9.3M lithium bromide solution and prepare sericin solution at 60°C. (S104) Dialysis to remove impurities; And (S105) reverse dialysis with 10% PEG 20000 solution to obtain a silk fibroin solution with a concentration of 6.0%.
7. The method for preparing an integrated amniotic membrane tubular porous scaffold according to claim 6, wherein step (S40) includes the following steps: (S401) A 6.0% silk fibroin / gelatin solution was freeze-dried to obtain a silk fibroin gelatin scaffold; (S402) was treated with 95% ethanol and 1% glutaraldehyde respectively to induce crystallization and chemical cross-linking; (S403) Process freeze-dried decellularized amniotic membrane to obtain decellularized amniotic membrane powder; (S404) Dissolve the decellularized amniotic membrane powder in a pepsin solution; (S405) Add 50 mg / mL of decellularized amniotic membrane solution to the silk fibroin gelatin scaffold, compress the scaffold wall between two flat iron objects, and then chemically crosslink it via EDC / NHS; and (S406) wash with distilled water and freeze-dry.
8. The method for preparing the tubular porous scaffold with integrated amnion according to claim 7, wherein in step (S405), the mass ratio of decellularized amnion:EDC:NHS is 1:1:0.
6.
9. A tubular porous scaffold integrating amnion, characterized in that, The integrated amnion tubular porous scaffold comprises decellularized amnion, gelatin, and silk fibroin, wherein the integrated amnion tubular porous scaffold is prepared by freeze-drying, compression, and cross-linking.
10. The application of the tubular porous scaffold with integrated amnion prepared by the preparation method according to any one of claims 1 to 8, characterized in that, The tubular porous stent with integrated amniotic membrane has the function of increasing urothelialization and inhibiting fibrosis, and can be used for scarless ureteral repair, ureteral defect repair, or ureteral reconstruction.